Duplicate cystic duct: A case report - Francino , Raíssa Paes; Martins , Eduarda Gomes; Prado , Abraão Rodrigues Valentim do; Frinhani, Mirelly Aparecida Nolasco; Franzin, Marcielle Grobério; Rosi, Maria Eduarda Almagro; Martins, Paula Gomes; Vasconcelos , Lívia Herundina Pontara de (Seven Editora, 2023)
INTRODUCTION: The cystic duct is one of the bile ducts responsible for the conduction of bile and together with the common hepatic duct make up the cystohepatic trine. The accessory hepatic ducts are those that have undergone anatomical variation and evaginate out of the liver. An example of this is the double cystic duct that presents with an incidence of 1 in 4,000 to 5,000 people. This duplication is classified as an exceptional surgical finding, and its diagnosis, for the most part, is made during surgery. It can even lead to iatrogenic lesions. This fact is justified mainly because its symptomatology is indistinguishable from cases in which there is no variation. CASE PRESENTATION: Patient V.M.S.N, 47 years old, complained of asthenia and epigastric pain for about two years. In consultation with the gastroenterologist, Upper Digestive Endoscopy was requested, which identified positivity for Helicobacter Pylori, hiatal hernia and moderate enanthematous gastritis. The patient was submitted to clinical treatment, but was unsuccessful. Upon returning to the doctor, a Total Abdomen Ultrasound was requested, which exposed mild hepatic steatosis, calculus in the left kidney, and cholelithiasis. Thus, she was referred to the general surgery outpatient clinic and laparoscopic cholecystectomy was indicated. During the surgical procedure, three structures confluent to the gallbladder were identified, opting for intraoperative cholangiography, which showed the presence of an accessory cystic duct. In view of the above, the cystic duct, accessory duct and cystic artery were repaired, and they were ligated. DISCUSSION: It is noted that this is an uncommon anatomical abnormality and is a great challenge for surgeons, marking the risk of iatrogenic lesions during the procedure. Therefore, the preoperative diagnosis and elucidation with the performance of intraoperative cholangiography are extremely important in order to avoid complications.  FINAL CONSIDERATIONS: The finding of accessory cystic duct is an atypical condition that exhibits clinical and radiological polymorphism and, therefore, of difficult preoperative diagnosis. Still, it was not observed in the literature the use of specific complementary tests that would lead to the early diagnosis of such pathology. Currently, the accurate diagnosis of cystic duct duplication is established intraoperatively in order to exclude lesions of the main biliary tract, which reduces the chances of the patient presenting complications, thus providing a better quality of life. DOI:https://doi.org/10.56238/innovhealthknow-012